1983
DOI: 10.1161/01.cir.67.4.807
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of captopril in chronic heart failure: a rest and exercise hemodynamic study.

Abstract: CONTROLLED TRIAL OF CAPTOPRIL IN CHF/Kramer et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1
2

Year Published

1984
1984
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(36 citation statements)
references
References 61 publications
1
32
1
2
Order By: Relevance
“…More recently, starting from imidazole derivatives Hofbauer & Wood, 1986). Prevention of the formation of first described by Furukawa et al (1982), it has been possible AII, via inhibition of ACE, has provided a powerful strategy to identify and characterize specific, nonpeptide, AII-receptor for the treatment of hypertension and congestive heart failure antagonists Carini et al, 1990; Wein- (Ondetti et al, 1977;Kramer et al, 1983;CONSENSUS stock et al, 1991;Biihlmayer et al, 1991;Mantlo et al, trial, 1987;Ondetti, 1991). Attempts to develop therapeutic 1991).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, starting from imidazole derivatives Hofbauer & Wood, 1986). Prevention of the formation of first described by Furukawa et al (1982), it has been possible AII, via inhibition of ACE, has provided a powerful strategy to identify and characterize specific, nonpeptide, AII-receptor for the treatment of hypertension and congestive heart failure antagonists Carini et al, 1990; Wein- (Ondetti et al, 1977;Kramer et al, 1983;CONSENSUS stock et al, 1991;Biihlmayer et al, 1991;Mantlo et al, trial, 1987;Ondetti, 1991). Attempts to develop therapeutic 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Two 12 week, parallel group, placebo-controlled studies of ACE inhibitors in heart failure (Franciosa et al, 1985;Kramer et al, 1983) showed significant improvement in exercise duration to or above ventilatory threshold, with a corresponding increase in oxygen consumption at the maximum level of exercise. In our older patients, exercising to first symptom, no improvement in minute ventilation, oxygen consumption or their ratio was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Captopril, an angiotensin converting enzyme inhibitor, produces haemodynamic and clinical benefits in patients with severe heart failure LeJemtel et al, 1982;Captopril Multicenter Research Group, 1983;Kramer et al 1983) but has not been shown to have established benefit over digoxin or diuretics in mild heart failure (Alicandri et al, 1986;Cowley et al, 1986;Magnani et al, 1986;The CaptoprilDigoxin Multicenter Research Group, 1988). Our own study compared captopril and ISDN as adjunctive treatment over 3 months in patients with mild heart failure already maintained on digoxin and diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Captopril produces clinical and haemodynamic benefits in the treatment of severe heart failure which is refractory to combined diuretics and digoxin therapy LeJemtel et al, 1982;Captopril Multicenter Research Group, 1983;Kramer et al, 1983). The benefits of captopril in mild heart failure and advantages over increased diuretic dosage have been less well defined with few long-term studies, no comparison with other vasodilators and no comparison of dosage frequency (Alicandri et al, 1986;Cowley et al, 1986;Magnani et al, 1986;Captopril-Digoxin Multicenter Research Group, 1988).…”
Section: Introductionmentioning
confidence: 99%